2017
DOI: 10.4193/rhin15.223
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy for allergic rhinitis: subjective versus objective tools to evaluate its success

Abstract: Changes in levels of allergen-specific Th2 cytokine-producing cells and IL-10+Foxp3+ cells could be objective biomarkers for SLIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Furthermore, in the placebo‐controlled clinical studies of SLIT for AR induced by cedar pollen using cedar pollen extract, the seasonal increase in cedar pollen‐reactive Th2 cytokine‐producing cells was suppressed by SLIT, while the number of IL‐10‐producing Treg cells increased after SLIT . These changes were associated with the clinical efficacy of SLIT . The difference between the results of the present study and those of previous studies might be due to the difference in allergen exposure or in the dispersal periods.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, in the placebo‐controlled clinical studies of SLIT for AR induced by cedar pollen using cedar pollen extract, the seasonal increase in cedar pollen‐reactive Th2 cytokine‐producing cells was suppressed by SLIT, while the number of IL‐10‐producing Treg cells increased after SLIT . These changes were associated with the clinical efficacy of SLIT . The difference between the results of the present study and those of previous studies might be due to the difference in allergen exposure or in the dispersal periods.…”
Section: Discussioncontrasting
confidence: 59%
“…Cedar pollenspecific IgE levels did not decrease with SLIT treatment for at least 18 months [10,12,26]. Allergen-specific immunotherapy does not improve allergic rhinitis induced by other allergens, demonstrating that SLIT does not inhibit the mast cell responses, which play important roles in allergic rhinitis, particularly in the early phase [27].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, these studies did not determine the potential interference of IgG4 in binding cedar pollen and pollen-specific IgE [29]. We previously showed that SLIT did not eliminate Th2 cells but instead inhibited the seasonal increase in cedar pollen-specific Th2 effector cells, which normally enhance allergic inflammation at the start of the dispersal season [11,26,30]. Although SLIT inhibited this enhancement, a longer period of suppression might be required to reduce the inflammation [11].…”
Section: Discussionmentioning
confidence: 99%
“…But it seems that not all allergen sIgG4s inhibit IgE binding to allergens, the epitope specificity and affinity of IgGs but not their isotype are decisive for their protective activity [28]. Maybe this could explain to certain extent why serum levels of allergen sIgG4s had no relationship with the clinical benefits [10,25,29]. Further, its bispecific activity makes it possible that allergen sIgG4 could oligomerize allergen molecules.…”
Section: Discussionmentioning
confidence: 99%